Physically Switchable Antimicrobial Surfaces and Coatings: General Concept and Recent Achievements - Elashnikov, Roman; Ulbrich, Pavel; Vokatá, Barbora; Pavlíčková, Vladimíra Svobodová; Švorčík, Václav; Lyutakov, Oleksiy; Rimpelová, Silvie (Nanomaterials (Basel, Switzerland), 2021)
Bacterial environmental colonization and subsequent biofilm formation on surfaces represents a significant and alarming problem in various fields, ranging from contamination of medical devices up to safe food packaging. Therefore, the development of surfaces resistant to bacterial colonization is a challenging and actively solved task. In this field, the current promising direction is the design and creation of nanostructured smart surfaces with on-demand activated amicrobial protection. Various surface activation methods have been described recently. In this review article, we focused on the "physical" activation of nanostructured surfaces. In the first part of the review, we briefly describe the basic principles and common approaches of external stimulus application and surface activation, including the temperature-, light-, electric- or magnetic-field-based surface triggering, as well as mechanically induced surface antimicrobial protection. In the latter part, the recent achievements in the field of smart antimicrobial surfaces with physical activation are discussed, with special attention on multiresponsive or multifunctional physically activated coatings. In particular, we mainly discussed the multistimuli surface triggering, which ensures a better degree of surface properties control, as well as simultaneous utilization of several strategies for surface protection, based on a principally different mechanism of antimicrobial action. We also mentioned several recent trends, including the development of the to-detect and to-kill hybrid approach, which ensures the surface activation in a right place at a right time.
Keywords: smart coatings; smart nanomaterials; biomedical applications; tailored surface; antimicrobial coatings; antifouling surface; physical stimuli